2016
DOI: 10.1159/000453035
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mechanisms Underlying the Therapeutic Effect of Glycomacropeptide on Allergy: Change in Gut Microbiota, Upregulation of TGF-β, and Inhibition of Mast Cells

Abstract: Background: The prevalence of allergic diseases is globally increasing. We have previously described that glycomacropeptide (GMP), a bioactive milk peptide, has therapeutic value in experimental models of skin hypersensitivity, anaphylaxis, and asthma, as it prevents an excessive T helper type 2 cell immune response. The aim of this study was to analyze the effect of GMP on key elements directly involved in the development or control of allergy, in order to improve the precise knowledge about its mechanism of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 43 publications
3
27
0
Order By: Relevance
“…Increase in Bacteroides population due to GMP-supplementation has been reported in mouse model studies 27,28 . Milk and subsequently GMP contain highly sialylated carbohydrate components 10 .…”
Section: Bacteroidetes Responsiveness To the Dairy Dietsmentioning
confidence: 82%
See 1 more Smart Citation
“…Increase in Bacteroides population due to GMP-supplementation has been reported in mouse model studies 27,28 . Milk and subsequently GMP contain highly sialylated carbohydrate components 10 .…”
Section: Bacteroidetes Responsiveness To the Dairy Dietsmentioning
confidence: 82%
“…Sawin et al 28 reported that a GMP-supplemented diet significantly decreased the caecal and colonic relative abundance of Desulfovibrio and Proteobacteria in wild type and PKU mice. Interestingly, GMP selectivity for promoting growth of Bacteroidetes taxa has also been reported 27,28 .…”
Section: Introductionmentioning
confidence: 94%
“…In recent years, a Mexican laboratory led by Salinas [55,[59][60][61] has focused on the study of the immunomodulatory activity of GMP in experimental allergy models. They found that oral administration of GMP to rats before and during sensitization with allergen significantly reduces the level of allergen-specific IgE in serum, and also decreases the proliferative response and the production of IL-13 by splenocytes stimulated by the allergen [55].…”
Section: The Immunomodulatory Properties Of Gmpmentioning
confidence: 99%
“…Animal models also indicate that Casein GMP could mediate intestinal inflammation via the gut microbiota [107–109], with administration associated with reductions in Proteobacteria, genera Desulfovibrio (from 30-35% to 7%), and increases in acetate, propionate and butyrate levels (cecum) [110]. Recent data proposed that GMP exerts anti-allergenic activity via modulation of gut microbiota [111]. Specifically, the GMP-induced increase in Lactobacillus , Bifidobacterium and Bacteroides , attributed to increased TGG-B production and reductions in mast cells [111].…”
Section: Nutraceuticalsmentioning
confidence: 99%
“…Recent data proposed that GMP exerts anti-allergenic activity via modulation of gut microbiota [111]. Specifically, the GMP-induced increase in Lactobacillus , Bifidobacterium and Bacteroides , attributed to increased TGG-B production and reductions in mast cells [111]. Clinical trials for active distal colitis in UC patients have reported casein GMP is well-tolerated, exerting similar disease-modifying effects to that of mesalazine [112, 113].…”
Section: Nutraceuticalsmentioning
confidence: 99%